Minimal Groups Increase Young Children's Motivation and Learning on Group‐Relevant Tasks. Issue 2 (17th October 2012) - Master, Allison; Walton, Gregory M.
Abstract : Three experiments ( N = 130) used a minimal group manipulation to show that just perceived membership in a social group boosts young children's motivation for and learning from group‐relevant tasks. In Experiment 1, 4‐year‐old children assigned to a minimal "puzzles group" persisted longer on a challenging puzzle than children identified as the "puzzles child" or children in a control condition. Experiment 2 showed that this boost in motivation occurred only when the group was associated with the task. In Experiment 3, children assigned to a minimal group associated with word learning learned more words than children assigned an analogous individual identity. The studies demonstrate that fostering shared motivations may be a powerful means by which to shape young children's academic outcomes.